2008
DOI: 10.1080/13674670701288639
|View full text |Cite
|
Sign up to set email alerts
|

Clergy work-related satisfactions in parochial ministry: The influence of personality and churchmanship

Abstract: The aim of this study was to test several hypotheses that clergy work-related satisfaction could be better explained by a multi-dimensional rather than a uni-dimensional model. A sample of 1071 male stipendiary parochial clergy in the Church of England completed the Clergy Role Inventory, together with the short-form Revised Eysenck Personality It has long been accepted that work is one of the more important domains of life to affect overall life satisfaction (Andrews & Inglehart, 1979;Campbell, Converse & Rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
2
7
1
Order By: Relevance
“…Eysenck and Eysenck style these factors as follows: the continuum from introversion through ambiversion to extraversion; the continuum from emotional stability through emotional lability to neurotic disorder; and the continuum from tendermindedness through toughmindedness to psychotic disorder. This model of personality has been employed among clergy by Francis and Rutledge (2000), Francis, Louden, and Rutledge (2004), Rutledge and Francis (2004), Francis, Turton, and Louden (2007), Turton and Francis (2007), and Francis, Hills, and Rutledge (2008). These studies agree that the clergy most vulnerable to burnout are introverts who also score high on the neuroticism scale, while the clergy most resilient to burnout are extraverts who score low on the neuroticism scale.…”
Section: Taking Personality Into Accountsupporting
confidence: 58%
“…Eysenck and Eysenck style these factors as follows: the continuum from introversion through ambiversion to extraversion; the continuum from emotional stability through emotional lability to neurotic disorder; and the continuum from tendermindedness through toughmindedness to psychotic disorder. This model of personality has been employed among clergy by Francis and Rutledge (2000), Francis, Louden, and Rutledge (2004), Rutledge and Francis (2004), Francis, Turton, and Louden (2007), Turton and Francis (2007), and Francis, Hills, and Rutledge (2008). These studies agree that the clergy most vulnerable to burnout are introverts who also score high on the neuroticism scale, while the clergy most resilient to burnout are extraverts who score low on the neuroticism scale.…”
Section: Taking Personality Into Accountsupporting
confidence: 58%
“…While other studies have found that women clergy are more satisfied with their work (Francis, Hills, & Rutledge, 2008;McDuff & Mueller, 2002), men in this study reported more career/vocation satisfaction. This appears to contradict earlier research, but it is likely that satisfaction with one's career is not equivalent to satisfaction with one's job, the variable in these other studies.…”
Section: Exploring the Gender Work Paradoxcontrasting
confidence: 55%
“…Clergy satisfaction is more multidimensional than unidimensional (Francis et al, 2008); so, satisfaction measures could be designed to look at various aspects of one's current position and one's career development. More direct measures of positive affect/engagement and negative affect/ burnout would also be useful.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Clergy make significant investments in learning about their faith tradition, and their work life and occupational identity is oriented around their religious community (Finke and Dougherty 2002;Ingram 1981;Mueller and McDuff 2004;Perl and Chang 2000). As clergy, they play many different roles that involve many distinct activities and responsibilities, ranging from preaching and teaching, to planning and administering congregational affairs, to pastoral visitations and counseling (Francis et al 2008;Kay 2000;Monahan 1999;Rowell 2000).…”
Section: Relevance For Clergy Mental Healthmentioning
confidence: 99%
“…Much of the work in this area has built on models of job burnout (Maslach et al 2001) that focus on the fit between the personality characteristics and the demands of congregational ministry (Francis and Rodger 1994;Francis et al 2008;Miner 2007a, b). Although this is a valuable approach, we take a different tack in this study, capitalizing on developments in: (a) the conceptualization and measurement of health-relevant domains of religiousness (e.g., Idler et al 2003), (b) growing interest in the religious and spiritual sources of clergy resilience as well as strain (e.g., Meek et al 2003), and (c) the marriage of religion-health research with the broader life-stress (or stress-and-coping) paradigm Fabricatore et al 2004).…”
Section: Introductionmentioning
confidence: 99%